2022
DOI: 10.3233/rnn-211176
|View full text |Cite
|
Sign up to set email alerts
|

Retinal nerve fiber and ganglion cell complex layer thicknesses mirror brain atrophy in patients with relapsing-remitting multiple sclerosis

Abstract: Background: Multiple sclerosis (MS) is associated with progressive brain atrophy, which in turn correlates with disability, depression, and cognitive impairment. Relapsing-remitting multiple sclerosis (RRMS) is a type of MS in which relapses of the disease are followed by remission periods. This is the most common type of the disease. There is a significant need for easy and low-cost methods to these cerebral changes. Changes in retinal layer thickness may reflect alterations in brain white and gray matter vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…In fact, in a study by Saidha et al, GC-IPL atrophy mirrored atrophy in the white matter, brainstem, grey matter, thalamus, and the whole brain. However, a recent study by Glasner et al suggested no correlation between white matter plaques and RNFL or GC-IPL thickness [ 17 ]. Nevertheless, grey matter atrophy seems to be the most sensitive marker of progressive MS [ 14 ].…”
Section: Optical Coherence Tomography In Multiple Sclerosismentioning
confidence: 99%
“…In fact, in a study by Saidha et al, GC-IPL atrophy mirrored atrophy in the white matter, brainstem, grey matter, thalamus, and the whole brain. However, a recent study by Glasner et al suggested no correlation between white matter plaques and RNFL or GC-IPL thickness [ 17 ]. Nevertheless, grey matter atrophy seems to be the most sensitive marker of progressive MS [ 14 ].…”
Section: Optical Coherence Tomography In Multiple Sclerosismentioning
confidence: 99%
“…Therefore, retinal and choroidal examinations have offered a new approach to investigate the development of neurologic diseases in recent decades. A co-atrophy pattern of the entire cerebral volume or a particular brain region and retinal thickness has been reported in the normal aging population [ 6 , 7 ] together with a variety of neurological diseases, including mild cognitive impairment [ 8 ], AD [ 9 , 10 ], Parkinson's disease [ 6 ], and multiple sclerosis [ 11 ] among others.…”
Section: Introductionmentioning
confidence: 99%
“…Even asymptomatic ON lesions, where patients have optic nerve lesions with no history of optic neuritis, are associated with a thinner RNFL and decreased visual contrast sensitivity, and transorbital ultrasonography suggests a decrease in ON diameter in MS patients [ 9 , 10 ]. RNFL and ganglion cell layer degeneration is correlated with decreased brain volume in MS patients, and OCT measurements have been used to monitor effectiveness of therapies in preventing retinal atrophy [ 11 , 12 , 13 , 14 ]. OCT, MRI, level of disability, and visual evoked potentials are all correlated with decreases in low contrast visual sensitivity in MS patients [ 15 ].…”
Section: Introductionmentioning
confidence: 99%